Implikasi Hukum Penghadap Yang Menolak Membubuhkan Sidik Jari Terhadap Pelaksanaan Kewajiban Notaris - Aswinabawa Wijaya, Gede Ivan; Dananjaya, Nyoman Satyayudha (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 02 (2024)DO - 10.24843/AC.2024.v09.i02.p04, 2024)
This writing’s purpose is to examine the role of Notary in responding to persons who refuse to put their fingerprints and examine the legal implications of persons who refuse to put their fingerprints on the implementation of the Notary's obligations. The method of this research is normative research method. The results of the research obtained are the role of Notary in responding to the applicant who refuses to put his fingerprints, namely that Notary must be able to give an explanation regarding the function of the fingerprint so that the applicant does not refuse and is willing to add his fingerprints and the legal implications of the applicant who refuses to add his fingerprints. Regarding the implementation of Notarial obligations, the deed made by the Notary remains valid also binding and has perfect evidentiary power as long as it meets the requirements written in Article 1868 and Article 1320 of the Civil Code, however, Notaries who violate this can be sentenced or subject to administrative sanctions